Farmer Exchange Rate, Government Spending On Education And Government Spending On Health of the Human Development Index in North Sumatra Province - Khairul Rizal; Zulkarnain Nasution; Junita Lubis (Gorontalo Development Review, 2021)
Human development is one of the factors in increasing the implementation of national development. Human development that is implemented can be calculated with the human level, health and standard of living. Then the level of the human development index can also affect government spending in the education sector and the health sector. The use of the model in this article with the multiple linear regression program is used to process, classical assumptions of test data using SPSS 22. The results of the analysis show that farmer exchange rates can significantly affect the human development index in North Sumatra Province, government spending in the education sector has a significant effect on the human development index in North Sumatra Province and government spending on health sector spending has no significant effect on human development index in North Sumatra Province. This shows that government spending in the health sector has not been properly realized so that it is not strong enough to increase the human development index in North Sumatra Province. The results of research on government spending in the education sector have a dominant effect in increasing the human development index in North Sumatra province.